CHANGING FORM OF TRIBAL ARTS - Dhama, Shalini (ShodhKosh: Journal of Visual and Performing Arts, 2023)
People generally consider tribal arts as synonymous with “rural culture” whereas it is the culture of those people who are part of a community. It is the product of human culture. India is a country full of many states, traditions and cultures. Tribal people of many religions and communities live in it. They have their own traditions and culture. Because every person lives in society and is an integral part of the society. Therefore, their activities and arts are also connected to the society. Folk art is considered to have originated with human life. Art has always been with man as his companion.